Paradigma Pendidikan Islam (Definisi, Arah, Dasar dan Ruang Lingkupnya) - Mohammad Riza Zainuddin (Tarbiyah Departement collaboration with AMCA, 2013)
Islamic education is one of the leading human empowerment, good thoughts, mental and moral, to undertake humanitarian functions performed as a form of a servant of God and also as a custodian of this universe. The definition of Islamic education is to determine the maximum of effort from the base personality of the students, as elaborated in the al-Quran and al-Sunnah. To the effect of the Islamic Education is shaping the personality of Islam, Islamic tsaqâfah master, master of science and technology (Science and Technology) Principles of Islamic education is the integration, balance, equality, education for life.